Navigating Corporate Social Responsibility for Sustainable Practices in the Shipping and Logistics Industry (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Corporate Social Responsibility (CSR) is becoming increasingly crucial for sustainable practices in the shipping and logistics industry, a sector known for its significant environmental and social impacts. This abstract explores the role of CSR in promoting sustainability within this industry, focusing on reducing carbon emissions, enhancing resource efficiency, and improving labor conditions. As the industry faces mounting pressure from regulators, consumers, and stakeholders to adopt more responsible practices, CSR initiatives provide a strategic framework for addressing these concerns. Key opportunities include the adoption of green technologies, such as fuel-efficient ships, renewable energy sources, and eco-friendly packaging, which help reduce the environmental footprint. Additionally, CSR extends to social aspects, such as promoting fair labor practices, fostering community engagement, and ensuring transparency in governance. However, challenges remain, including regulatory compliance, rising operational costs, and the complexity of aligning global supply chains with CSR goals.